Determinants for cap trimethylation of the U2 small nuclear RNA are not conserved between Trypanosoma brucei and higher eukaryotic organisms - Günzl, Arthur (Oxford University Press, 2000)
In most eukaryotic organisms the U2 small nuclear RNA (snRNA) gene is transcribed by RNA polymerase II to generate a primary transcript with a 5′ terminal 7-methylguanosine cap structure. Following nuclear export, the U2 snRNA is assembled into a core ribonucleoprotein particle (RNP). This involves binding a set of proteins that are shared by spliceosomal snRNPs to the highly conserved Sm site. Prior to nuclear import, the snRNA-(guanosine-N2)-methyltransferase appears to interact with the core RNP and hypermethylates the cap structure to 2,2,7-trimethylguanosine (m(3)G). In the protist parasite Trypanosoma brucei, U-snRNAs are complexed with a set of common proteins that are analogous to eukaryotic Sm antigens but do not have a highly conserved Sm sequence motif, and most U-snRNAs are synthesised by RNA polymerase III. Here, we examined the determinants for m(3)G cap formation in T.brucei by expressing mutant U2 snRNAs in vivo and assaying trimethylation and RNP assembly by immunoprecipitation. Surprisingly, these studies revealed that the Sm-analogous region is not required either for binding of the common proteins or for cap trimethylation. Furthermore, except for the first 24 nt which are part of the U2 promoter, the U2 coding region could be substituted or deleted without affecting cap trimethylation.